Cluster randomised controlled trial of a multicomponent intervention to support the implementation of policies and practices that promote healthier environments at junior sports clubs: study protocol. Issue 1 (23rd January 2018) - Milner, Sharin; Sherker, Shauna; Clinton-McHarg, Tara; Dray, Julia; Zukowski, Nadya; Gonzalez, Sharleen; Kingsland, Melanie; Ooi, Jia Ying; Murphy, Allan; Brooke, Daisy; Wiggers, John; Wolfenden, Luke
Abstract : Introduction: A large proportion of children and adolescents participate in organised sport, making community sports clubs a promising setting to support healthy behaviours. To date, however, there have been few interventions conducted in junior sports clubs that have targeted health-promoting practices. The primary aim of this pilot study is to assess the potential effectiveness of an intervention to implement health-promoting policies and practices in junior sporting clubs targeting alcohol and tobacco practices, healthy food and beverage availability, and physical activity via participation in sport. A secondary outcome is to assess the impact of such strategies on child exposure to alcohol and tobacco use at the club, purchasing behaviours by/for children at the club canteen and child sports participation opportunities. Methods and analysis: The study will employ a cluster randomised controlled trial design and be conducted in metropolitan and regional areas of two Australian states. Randomisation will occur at the level of the football league. Community football clubs with over 40 junior players (players under 18 years) within each league will be eligible to participate. The intervention will be developed based on frameworks that consider the social, cultural and environmental factors that influence health behaviours. Intervention clubs will be supported to implement 16 practices targeting alcohol management, tobacco use, nutrition practices, new player recruitment activity, equal participation for players and the development of policies to support these practices. Trained research staff will collect outcome data via telephone interviews at baseline and follow-up. Interviews will be conducted with both club representatives and parents of junior players. Ethics and dissemination: The study has been approved by the University of Newcastle Human Research Ethics Committee (H-2013-0429). The results of the study will be disseminated via peer-reviewed publications and presentations at conferences. Trial registration number: ACTRN12617001044314; Pre-results .